HUBUNGAN ANTARA PERILAKU KEKERASAN SEKSUAL DENGAN KONDISI LINGKUNGAN FISIK DI KAMPUS UNPAD JATINANGOR: SUDUT PANDANG MAHASISWA - Gumilang Ramadhan; Arinda Putri Wulandari; Nurliana Cipta Apsari (Jurnal Ilmiah Rehabilitasi Sosial (Rehsos), 2023)
Sexual violence is a hot issue at Padjadjaran University, the emergence of accounts on social media containing photos of perpetrators of sexual violence and the formation of the SATGAS PPKS which focuses on handling sexual violence cases is clear evidence that this issue does occur in the campus environment. Cases of sexual violence on the Unpad Jatinangor campus are also considered to still not get maximum treatment so that there are still many cases that are not resolved properly, this is influenced by the flow of complaints that are not known by the entire academic community, including students. Sexual violence that occurs on campus is also supported by several factors such as campus environmental conditions. This study aims to examine the relationship between physical conditions and the environment with sexual violence at Campus Unpad Jatinangor by referring to Stimulation Theory and Behavioral Setting Theory. The method used in this study is a qualitative research method . The results of the study explained that sexual violence is influenced by the physical environment of the campus which is quiet, dark and difficult to reach security posts, as well as the lack of maintenance and the availability of facilities and infrastructure such as CCTV. Streets along the SOSHUM and SAINTEK clumps, building alleys and toilets are some of the points that have the potential to become places for sexual violence to occur. Real action and contributions from various elements are needed so that this issue can get priority to get the right treatment. Such as improving facilities and infrastructure or comprehensive and continuous socialization regarding efforts to prevent and handle cases of sexual violence. Keywords: Environment, Sexual Violence, Stimulation Theory, Behavioral Setting Theory, Unpad Jatinangor